The effects of a brief hypnosis intervention on self-confidence in professional team handball players - Rathschlag, M.; Lind, E.; Kennedy, G.; Morris, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Modern practices of hypnosis have occurred most commonly in the fields of medicine, dentistry, and psychology. However, the implementation of hypnosis into the field of sport psychology is still undeveloped and there are only a few studies in this research field (e.g. Barker, Jones, & Greenless, 2010; Pates, Cummings, & Maynard, 2002). The aim of the study was to increase our understanding whether a hypnosis intervention can help athletes to enhance their self-confidence. Methods: Participants were selected from a professional team handball team in Germany (n = 18). A pretest-posttest follow-up design with repeated measures was used. The players were randomly assigned to either a hypnosis (n = 9) or a progressive muscle relaxation group (n = 9). All participants undertook four training sessions (of either hypnosis or progressive muscle relaxation) in between pretest (baseline) and the posttest data collection. All participants completed the self-confidence subscale of the CSAI-2, the SSCI and the TCSI at both times of measurements. Results: The results showed a significant main effect for time of measurement in the SSCI (F(1,16) = 5.355, p < .036) and also in the CSAI-2 (F(1,16) = 3.788, p < .048). There were no significant main effects for group and no significant interactions in the different scales. Discussion: Results indicated that both a hypnosis intervention and a progressive muscle relaxation can help athletes to enhance their state self-confidence. Further studies can investigate the temporal stability of this effect over a longer period.